Dėl kuršių kalbos palikimo - Mažiulis, Vytautas (Baltistica, 2008)
ON THE HERITAGE OF CURONIAN Lithuanian dial. aukà / aũkas “Opfer” (“victim, sacrifice”) is from Lith. alkà / al̃kas “Hain”, which is from Balt. *alkā / *alkas „Hain“, which along with Goth. alks „Hain“ suggests that I.-E. *alk- „Hain“, is most likely derived from the I.-E. verb *alk- (: *alek-) „to preserve, protect“. Perhaps the I.-E. verb *ol- / *el- „to flow“, “to twist, meander“ is hidden in it. The Samogitian hill Girgždū̃tė is in the place of the older Girgždutà < Cur. *Girzdutā, which is mobile subst. (fem.) *girzdutā „that (stream), which gurgles, babbles“ ← verb. Cur. *girzd- „to gurgle“, a derivative from subst. Cur. *girzda- „gurgle, gravel“. Criticism is provided against the traditional opinion, that the name of the hill Cur. *Girzdutā is attested inaccurately to in historical sources (XIV–XV centuries). The settlement Lith. (Žem.) Krãžiai, as the plur. collectivum, presupposes the former Cur. river/settlement *Kraźā́ from onomatopoetic Cur. (mobile subst.) *kraźā́ „the murmurer“ ← verb. Cur. *kreź- / *kraź- „to murmur“. Afterwards, when the river *Kraźantē appeared, the form *Kraźā́ from river / settlement turned into the settlement name *Kraźā́. The issue of the West Balt. (and Cur.) words for „ant“ are touched upon. First of all Prus. (E 791) sangis „ant“, is most likely from *zangis „speedy one“; further on the Lith. skruzdìs „ant“ is discussed. Also discussed is the Curonian origin of the Žem. place names Šatrijà and Var̃niai, and evidence is given, that the latter appeared not from the word „varna (crow)“ which is the traditionally held view, but from „that, which is blackish“.